2021
DOI: 10.1177/07340168211052876
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19's Impact on Probation Professionals’ Views About Their Roles and the Future of Probation

Abstract: In 2020, the COVID-19 global pandemic forced probation departments to change their practices overnight. The phenomenon presented many challenges for probation departments but also opened avenues for innovation and changes in attitudes toward supervision practices. We surveyed adult and juvenile probation departments in the entire state of Texas, specifically targeting management and supervisory personnel, officers with caseloads, including court officers, and information technology personnel ( N = 1,353). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…We argue that the use of remote supervision is not a panacea. The emerging research suggests a number of benefits to the use of remote supervision (see Lockwood et al, 2021 ; Martin & Zettler, 2021 ; Sturm et al, 2021 ), but it is not without limitations. Beyond disparities in access to technology (Martin & Zettler, 2021 ; Phillips et al, 2021 ), potential disadvantages include the loss of in-person interaction with co-workers and clients (Stempkowski & Grafl, 2021 ), struggles in holding clients accountable (Lockwood et al, 2021 ) and difficulties conducting risk assessments (Phillips et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue that the use of remote supervision is not a panacea. The emerging research suggests a number of benefits to the use of remote supervision (see Lockwood et al, 2021 ; Martin & Zettler, 2021 ; Sturm et al, 2021 ), but it is not without limitations. Beyond disparities in access to technology (Martin & Zettler, 2021 ; Phillips et al, 2021 ), potential disadvantages include the loss of in-person interaction with co-workers and clients (Stempkowski & Grafl, 2021 ), struggles in holding clients accountable (Lockwood et al, 2021 ) and difficulties conducting risk assessments (Phillips et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging research suggests a number of benefits to the use of remote supervision (see Lockwood et al, 2021 ; Martin & Zettler, 2021 ; Sturm et al, 2021 ), but it is not without limitations. Beyond disparities in access to technology (Martin & Zettler, 2021 ; Phillips et al, 2021 ), potential disadvantages include the loss of in-person interaction with co-workers and clients (Stempkowski & Grafl, 2021 ), struggles in holding clients accountable (Lockwood et al, 2021 ) and difficulties conducting risk assessments (Phillips et al, 2021 ). Moreover, although some officers have indicated remote supervision can increase client engagement (Norton, 2020 ), others have found that remote contacts pose engagement challenges, particularly for newer clients (Phillips et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-release probationary period commonly includes frequent check-ins with probation officers, drug tests, and participation in reentry services, such as mental health, parenting, education, and employment programs. Recent literature suggests that the COVID-19 pandemic altered the nature of probation services (Martin & Zettler, 2022 ). In many regions, in-person probation check-ins were replaced with remote communication such as telephone calls, video conferences, emails, and text messages (Schwalbe & Koetzle, 2021 ).…”
Section: Probation and Reentry Services During Covid-19mentioning
confidence: 99%
“…Like most non-critical activities, Scottish probation offices were closed, and essential personnel and their staff were required by their employing local authorities to, where possible, work from home. In these circumstances, Scottish probation services and their staff had to innovate (Martin and Zettler, 2022), in particular by working remotely (Dominey et al, 2021; Phillips et al, 2021), whilst being isolated from each other and working in conditions that were highly uncertain, alarming and indeed, life threatening. This has raised questions regarding how Criminal Justice managers reacted.…”
Section: Introductionmentioning
confidence: 99%